Platelet Survival in Patients with Angiographically Diseased and Normal Coronary Arteries - Verhaeghe, R; Piessens, J; Suy, R; Verstraete, M (Thrombosis and Haemostasis, 1984)
Platelets may contribute to the pathogenesis of atherosclerosis and to the complications of coronary artery disease. Therefore, platelet kinetics were studied in 69 patients with angiographically documented coronary artery disease and in 16 patients with a normal coronary angiogram. Platelet survival time was calculated from the decay of radioactivity after injection of 51Cr-labeled autologous platelets. None of the mathematical models used was able to discriminate between the two patients groups. No correlation existed between survival time and extent of the arterial disease. Patients with a high serum cholesterol did not exhibit an enhanced platelet consumption. Thus, these studies do not support the idea that platelet turnover is enhanced in patients with coronary artery disease as compared to those with normal coronary arteries.
Keywords: Blood platelets; Coronary disease; Angina pectoris; Arteriosclerosis